7 - Projets de développement en Afrique subsaharienne, entre changement social et normes sociales : l’agent du développement à l’épreuve du terrain - Ossere NGANONGO (African Sociological Review, 2019)
The economic and social situation in Sub – Saharan Africa is globally worrying, with economic crises, conflicts leading to poverty and precariousness, epidemic and endemic diseases. Governments, UN agencies and NGOs and other international solidarity organizations are at the heart of important issues requiring interventions able to resolve situations and avoiding humanitarian tragedies. These interventions, resulting from strategies and plans in the form of development projects, most often benefit societies and communities with traditions sometimes resistant to the social transformations deemed essential for human well – being and social change. Thus, the actor, moreover trained and experienced, driven by a desire to bring change in a situation diagnosed as precarious, is caught between the mission of development agent and the social norms which govern and regulate behaviors within a given society. The actor is faced with situations not foreseen by academic curriculum and must use common sense to achieve the expected objectives by developing strategies of infiltration of communities to influence, from within, social norms, without shaking local traditions, thus enabling planned activities.